2005
DOI: 10.1159/000085747
|View full text |Cite
|
Sign up to set email alerts
|

E-Test: An Alternative Method for Susceptibility Testing of <i>Mycobacterium tuberculosis</i>

Abstract: Objective: The purpose of this study was to compare the agar proportion method with the E-test method for susceptibility testing of Mycobacterium tuberculosis.Materials and Methods: A total of 100 isolates were tested for isoniazid, rifampin, streptomycin and ethambutol susceptibility using an indirect-proportion method as well as the E-test method. Results:Categorical agreement between the methods was 100% for isoniazid, rifampin, streptomycin, and ethambutol. Conclusion: The E-test method appears to be an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…In the se stu di es, E test met hod was empha si zed as a fast, easy, re li ab le, and fe a sib le method for ro u ti ne use in de tec ting an timy co bac te ri al sus cep ti bi lity. 11,12,19,21,24 Ak ca li et al ha ve al so found an ex cel lent ag re e ment for INH, RIF, SM and EMB (100%) with E test and agar pro por ti on results in the ir study. 19 In anot her study, Mu ra lid har et al sug ges ted that cor re la ti on bet we en L-J propor ti on and E test met hod was 87%.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In the se stu di es, E test met hod was empha si zed as a fast, easy, re li ab le, and fe a sib le method for ro u ti ne use in de tec ting an timy co bac te ri al sus cep ti bi lity. 11,12,19,21,24 Ak ca li et al ha ve al so found an ex cel lent ag re e ment for INH, RIF, SM and EMB (100%) with E test and agar pro por ti on results in the ir study. 19 In anot her study, Mu ra lid har et al sug ges ted that cor re la ti on bet we en L-J propor ti on and E test met hod was 87%.…”
Section: Discussionmentioning
confidence: 85%
“…11,12,19,21,24 Ak ca li et al ha ve al so found an ex cel lent ag re e ment for INH, RIF, SM and EMB (100%) with E test and agar pro por ti on results in the ir study. 19 In anot her study, Mu ra lid har et al sug ges ted that cor re la ti on bet we en L-J propor ti on and E test met hod was 87%. 25 Ho we ver, Fre i xo et al and Ha us dor fer et al no ted a sig ni ficant num ber of fal se sen si ti ve and fal se re sis tant re sults with E test in com pa ri son with agar propor ti on.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Etest (AB Biodisk, Solna, Sweden) is used for quantitative antibiotic susceptibility testing of numerous microorganisms, including various species of mycobacteria, including M. tuberculosis (1,2,(12)(13)(14)(15)(17)(18)(19)(20). The current recommended Etest procedure for M. tuberculosis is based on Middlebrook 7H11 agar supplemented with oleic acid, albumin, dextrose, and catalase (OADC) (1).…”
mentioning
confidence: 99%